Crystallographic and docking (Cathepsins B, K, L and S) studies on bioactive halotelluroxetanes - Caracelli, Ignez; Maganhi, Stella H.; de Oliveira Cardoso, Josiane; Cunha, Rodrigo L.O.R.; Vega-Teijido, Mauricio Angel; Zukerman-Schpector, Julio; Tiekink, Edward R. T. * (2018)
The molecular structures of the halotelluroxetanes p-MeOC6H4Te(X)[C(=C(H)X′)C(CH2)nO], X=X′=Cl and n=6 (1) and X=Cl, X′=Br and n=5 (4), show similar binuclear aggregates sustained by {· · ·Te–O}2 cores comprising covalent Te–O and secondary Te· · ·O interactions. The resulting C2ClO2(lone-pair) sets define pseudo-octahedral geometries. In each structure, C–X· · ·π(arene) interactions lead to supramolecular layers. Literature studies have shown these and related compounds (i.e. 2: X=X′=Cl and n=5; 3: X=X′=Br and n=5) to inhibit Cathepsins B, K, L and S to varying extents. Molecular docking calculations have been conducted on ligands (i.e. cations derived by removal of the tellurium-bound X atoms) 1′–3′ (note 3′=4′) enabling correlations between affinity for sub-sites and inhibition. The common feature of all docked complexes was the formation of a Te–S covalent bond with cysteine residues, the relative stability of the ligands with an E-configuration and the formation of a C–O· · ·π interaction with the phenyl ring; for 1′ the Te–S covalent bond was weak, a result correlating with its low inhibition profile. At the next level differences are apparent, especially with respect to the interactions formed by the organic-ligand-bound halides. While these atoms do not form specific interactions in Cathepsins B and K, in Cathepsin L, these halides are involved in C–O· · ·X halogen bonds.